Compact Low-Power-Consumption 28-Gbaud QPSK/16-QAM Integrated Silicon Photonic/Electronic Coherent Receiver - J. Zhang; J. Verbist; B. Moeneclaey; J. Van Weerdenburg; R. Van Uden; H. Chen; J. Van Campenhout; C. Okonkwo; X. Yin; J. Bauwelinck; G. Roelkens (IEEE Photonics Journal, 2016)
We demonstrate the codesign and cointegration of an ultracompact silicon photonic receiver and a low-power-consumption (155 mW/channel) two-channel linear transimpedance amplifier array. Operation below the forward error coding (FEC) threshold both for quadrature phase-shift keying (QPSK) and 16-quadrature amplitude modulation (QAM) at 28 Gbaud is demonstrated.